Desempenho agronômico de híbridos de minitomate em diferentes sistemas de condução e número de hastes - Vargas, Pablo F. [UNESP]; Duarte, Leonardo S. [UNESP]; Silva, Edgard H. C. [UNESP]; Zecchini, Amanda C. [UNESP]; Soares, Renato S. [UNESP]; Godoy, Leandro J. G. [UNESP] (FapUNIFESP (SciELO), 2017)
At present, Brazil is among the world’s largest tomato producers. This production is directed both for the industry and for fresh consumption. Among the different tomato groups, production of minitomatoes has grown in recent years because of their high commercial value and mainly greater price stability. However, there are few studies investigating the proper management of this group, as it is recent in the country. The aim of the present study was to evaluate the viability of mini-tomato hybrids in different training systems, in greenhouse conditions. The experiment was set as a randomized block design in a 2×2×4 factorial arrangement with two numbers of stems (one and two stems per plant), two training systems [conventional (vertical) and horizontal], and four hybrids [AF 18196 (Sakata Seed); AF 13106 (Sakata Seed); Nina (Takii Seed) and Cocktail Mascot (Agristar/Top Seed Premium)], with three replicates and four plants per plot in the usable area. The evaluated variables were production per plant, fruit weight, transverse and longitudinal fruit diameter, number of fruits per plant, number of clusters per plant, number of fruits per cluster, precocity, production cycle, chlorophyll index, soluble solids, and crop cycle. The most promising hybrids are AF 13106 (2.71 kg/plant), AF 18196 (2.63 kg/plant) and Mascot (2.38 kg/plant), managed with two stems (2.63 kg/plant), in the vertical system (2.94 kg/plant).
Performance of mini-tomato hybrids in different training systems with different number of stems
Keywords: Genotype × environment interaction; Solanum lycopersicon; Tomato management